HUMAN ECOLOGY AND THE BIOSPHERE THAT AFFECTS IT (World Bulletin of Public Health, 2022)
This article discusses issues related to human ecology, the origin of anthropoecological systems, living conditions, development and their relationship with the environment, as well as the dynamic relationship of the anthropoecological system with the environment and its satisfaction in this environment
Keywords: anthropoecological system; biosphere; migration; radiation